Terapi Aktivitas Kelompok dengan Terapi Tebak Benda Terhadap Lansia untuk Mengatasi Penurunan Fungsi Kognitif di Panti Werdha Kasih Ayah Bunda - Safitri, Alfika; Juliyati, Anisa; Permatha Indah, Gia Sastri; Perdana, Daffa Affan; Syahrul Karim, Muhammad; Mubarok, Deby; Valentine, Geni; Hermawati, Anisa (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: The elderly are one of the population at risk groups that are increasing in number. Saying that the population at risk is a group of people whose health problems are likely to worsen due to influencing factors. According to the World Health Organization (WHO), elderly people refer to the population group aged 60 years and over. Objective: The goal of the guessing object group activity therapy is to improve cognitive abilities. Method: The group has 3 stages, namely orientation, work stage and provision of guessing object therapy, where before starting we conduct a pre-test to measure the patient's level of knowledge of guessing object therapy and after finishing guessing objects we conduct a post-test. Result: Based on the results of this observation, it was obtained after conducting group activity therapy of guessing objects, the results of the post-test were that participants (80%) had a good level of knowledge, while 2 participants (20%) were still in the category of poor knowledge. Conclusion: Group activity therapy Guess the Object can improve cognitive abilities, social interaction, self-confidence, and problem-solving skills, as well as provide fun and relaxation for participants. This activity can be one of the effective therapy options to improve the quality of life and well-being of individuals or groups.